Diethyldithiocarbamate Delayed Wound-Induced Callus Formation in Potato Tubers by Inhibiting Superoxide Dismutase - CHENG Xinyan, SONG Bingfang, LIU Ning, TIAN Wenmao, YIN Yan, LI Yongcai, BI Yang, WANG Yi (Shipin Kexue)
In this study, potato tubers (Solanum tuberosum L.) were artificially damaged and then soaked in 10 mmol/L diethyldithiocarbamate (DDC) solution, an inhibitor of superoxide dismutase (SOD). We determined the StSODs gene expression and activity of SOD, reactive oxygen species (ROS) content, phenylpropanoid metabolism-related enzyme activity, total phenols and lignin contents at the wound site during the healing process. In addition, the deposition of suberin polyphenolic (SPP) and lignin were observed. The results showed that DDC treatment downregulated StSODs expression, suppressed SOD activity, reduced the content of H2O2, and decreased the activities of phenylalanine ammonia lyase (PAL) and peroxidase (POD) as well as the contents of total phenols and lignin compared with the control. After 1 day of healing, the expression of StCSD1, StFSD3 and StMSD in the treated tubers were 31.90%, 69.30% and 61.83% lower than those of the control, respectively. In addition, SOD activity, H2O2 content, PAL and POD activity were 36.17%, 15.38%, 28.20% and 24.90% lower than those of the control, respectively. The deposition of SPP and lignin were delayed by DDC treatment. After 7 days of healing, the thicknesses of the SPP and lignin layers in the treated tubers were 16.84% and 23.00% lower than those of the control, respectively. In summary, DDC treatment downregulated StSODs expression during the healing process, inhibited the activity of SOD, reduced H2O2 content, weakened phenylpropanoid metabolism, and delayed the accumulation of SPP and lignin at the wound site of potato tubers. Therefore, the effect of DDC on delaying callus formation in wounded potato tubers is closely related to its inhibitory effect on H2O2 production catalyzed by SOD.